Analysis and generalization of experience in the implementation of engineering services in the implementation of investment and construction projects in Kiev - Voronyuk, Y. (Ways to Improve Construction Efficiency, 2021)
The article analyzes and summarizes the experience of providing engineering services, namely, customer service in the implementation of investment and construction projects in Kiev. As practical experience shows, most customers tend to have their own customer service in their structure, and despite its presence, the overwhelming majority of them are not satisfied with the results. «Сompany Basis» has conducted a significant number of audits of already implemented investment and construction projects for such companies as Intergalbud, Kievgorstroy, Geos, Brocard and many other companies and private customers. As a result of data analysis, similar problems and difficulties were identified. The main problems are that quite often, in such structures, the attitude to the organization and control of processes is quite nominal. That is, as a rule, there is an algorithm of interaction of all employees, but it is not always followed. At the same time, company executives most often approach such an algorithm from the standpoint. First, they believe that once such a description of all procedures is available, then everyone, of course, performs it. But there is no verification of how exactly employees follow this algorithm. The second option – managers do not take into account the existence of such a mechanism, and when managing the company are guided by the methods to which they are accustomed. And it happens that they try to keep all the details under personal control, even the least important ones. As a result, the manager is very busy, and the expected result is absent. So what needs to be done? It is necessary to develop a clear and understandable road map that takes into account all the nuances of a particular construction project. In the future, implement it in the company's milestones. And in the future to control that all carried out it. If any of the nuances of those. Or other reasons are not taken into account, add it to the existing algorithm and update it as follows. At the same time, there is an understanding that not all employees are ready to unquestioningly adhere to it because everyone has their own experience and is guided by it. For example, it may turn out that the cumulative statement of the volume of work performed is not kept. Either the executive documentation is not kept in the number of copies or not in the form required for delivery and further operation of the object. Thus, it becomes quite clear that a new approach is needed to solve the existing problem. Such a tool is the customer service of the second level, which includes the development of a clear and understandable roadmap, implementation and control of its implementation at all stages of the project.